Clinical islet isolation and transplantation outcomes with deceased cardiac death donors are similar to neurological determination of death donors. (3rd September 2015) - Andres, Axel; Kin, Tatsuya; O'Gorman, Doug; Livingstone, Scott; Bigam, David; Kneteman, Norman; Senior, Peter; Shapiro, A. M. James
Summary: In islet transplantation, deceased cardiac death (DCD) donation has been identified as a potential extended source. There are currently no studies comparing outcomes between these categories, and our goal was to compare islet isolation success rates and transplantation outcomes between DCD and neurological determination of death (NDD) donors. Islet isolations from 15 DCD and 418 NDD were performed in our centre between September 2008 and September 2014. Donor variables, islet yields, metabolic function of isolated isled and insulin requirements at 1‐month post‐transplant were compared. Compared to NDD, pancreata from DCD were more often procured locally and donors required less vasopressive support ( P < 0.001 and P = 0.023, respectively), but the other variables were similar between groups. Pre‐ and postpurification islet yields were similar between NDD and DCD (576 vs. 608 × 10 3 islet equivalent, P = 0.628 and 386 vs. 379, P = 0.881, respectively). The metabolic function was similar between NDD and DCD, as well as the mean decrease in insulin requirement at 1‐month post‐transplantation (NDD: 64.82%; DCD: 60.17% reduction, P = 0.517). These results support the broader use of DCD pancreata for islet isolation. A much larger DCD islet experience will be required to truly determine noninferiority of both short‐ and long‐term outcomes.